Upswing in Europe gains momentum, but unemployment remains high - Klaus-Jürgen Gern; Joachim Scheide; Markus Schlie (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
The expansion of Western European production accelerated in the first half of 1997. Exports were the main engine, driven by a devaluation of European currencies and strong growth abroad. Domestic demand also picked up somewhat led by investment in machinery and equipment. Inflation remained at low levels. However, in most countries the bottom seems to have been reached. One major concern is the rise in import prices. The upswing will further gain momentum in the coming months and in 1998 as conditions shaping the cycle remain favorable. Real GDP in Western Europe will increase by 3 percent in 1998. Under the assumption that the decision concerning EMU due in spring 1998 is made in favor of a large monetary union, those countries with relatively high short-term interest rates will lower them quite substantially in next year. Against the background of high unemployment, countries with low interest rates will not raise key interest rates significantly. As a consequence, monetary policy in Western Europe on average will be further loosened. This will additionally stimulate economic activity but also raise risks of inflation. The major problem in Western Europe is unemployment, which remains stubbornly high or is even rising. As a contrast, unemployment in the United States has come down to the lowest level since decades. It is often stated that high unemployment in Europe is due to a restrictive monetary policy, led by a—supposedly—deflationary policy pursued by the Deutsche Bundesbank. This view, however, does not find any support when indicators of monetary policy are taken into account. Rather, they suggest that monetary policy has been expansionary in Europe for some time. In addition, the reduction of inflation since 1990 has been equally pronounced in Europe and the United States, which indicates that the monetary stance has not been significantly different. Furthermore, a striking fact in this regard is that the relatively steep fall of inflation in the United Kingdom was associated with a significant decline in unemployment. While total unemployment in Europe has followed an upward trend resulting in an approximate doubling of the rate, there have been notable exceptions within Europe. Among those economies that have experienced a decline in recent years are the United Kingdom, the Netherlands and Ireland; other countries seem to have joined the club. Overall, a variety of measures has contributed to the improvement of labor market performance in these countries. They include deregulations of product and labor markets that have led to wage moderation and more wage differentiation, and reforms of the tax and transfer systems that have resulted in improved incentives for both labor demand and labor supply. A central feature of individual countries' experience is that reforms tend to be more effective when they are comprehensive since there are important synergies between structural reforms in different fields.
Keywords: 330; Konjunktur; Konjunkturprognose; Arbeitslosigkeit; Geldpolitik; Europa; Deutschland; Frankreich; Italien; Großbritannien